KESIAPAN PEMBELAJARAN TATAP MUKA DAN KESEHATAN MENTAL SISWA SEKOLAH DASAR AKIBAT PEMBELAJARAN DARING - Della Novita Sari; Fatdilah Nuraini Alfansuri; Risa Qurotun Aini; Muhammad Nurkapid; Arum Tunjung Wulandari (Academica: Journal of Multidisciplinary Studies, 2021)
Indonesia has entered a decline in Covid-19 cases. Based on this, the government is considering implementing the Face-to-Face Learning (PTM) process in early 2021. Readiness for the implementation of PTM carried out in schools must pay attention to readiness from an internal and external perspective. The readiness for the implementation of PTM from an internal perspective is the support from parents and teachers. This support can be in the form of managing the child's stress, encouragement to express the child's feelings, as well as important mental support for the child. This study uses a qualitative research approach. The method used is literature study and the data collection method is in the form of documentation. This study was used to understand the mental health of elementary school students in dealing with the implementation of PTM. The analytical method used in this study is the AHP (Analytic Hierarchy Process) method. The readiness for the implementation of PTM on the mental health of elementary school students can be handled in three ways, namely providing students with knowledge about Covid-19, knowing their own health conditions and being able to take steps according to their own health conditions. The readiness for the implementation of PTM from schools greatly affects the mental health of children. Therefore, there is a need for careful preparation both internally and externally.Keywords: Face-to-face Learning Readiness; Mental health; Elementary School Student